Tourist perceptions, motivations and expectations when interacting with African lion (Panthera leo) cubs - Ann Wilson; Clive JC Phillips (Animal Welfare)
Tourism wildlife interactions are controversial, the debate hinging largely on the compromised welfare of the animals used. Despite this, lion cub (Panthera leo) interactions are popular, and there is a need to understand what motivates interactors to participate in the activity, their perceptions and expectations. We surveyed the attitudes of 300 visitors to three lion cub interaction facilities in South Africa. Whilst 38% of interactors were aware of the controversy around lion cub interactions, 69% desired the experience regardless. It is widely assumed that lion cub interaction opportunities are big attractions, yet 74% of respondents said that they would still have visited if lion cub interactions were not offered. Whilst 84% of interactors felt that their expectations were met, 61% said that the interaction had no impact on them. Several of those interviewed interacted with multiple species, and 34% determined that their favourite engagement was with animals that interacted back voluntarily. Most of those interviewed chose the interaction for their children (69%). Whilst 58% felt the experience was educational, only 2% of these had learnt about the plight of lions in the wild. When asked to reflect on the welfare of the lion cubs they had interacted with, ‘Freedom from discomfort’ was seen as the most important factor, as well as ‘Freedom to express natural behaviour’. Interactions were viewed with a variety of emotions and generated a range of beliefs. We conclude that the findings can be used by facilities to better prepare visitors for the experience, ensuring that interaction animals are better able to serve in their role as ambassador representatives.